THU0633-HPR The Effects of a Free Weight Based Strength Training Intervention on Pain, Lumbar Fat Infiltration and Biomechanics. (9th June 2015) - Welch, N.B.; Falvey, E.; Franklyn-Miller, A.; Moran, K.; Coyle, J.; Antony, J.; Gore, S.; Richter, C.
Abstract : Background: Chronic low back pain is one of the most prevalent musculoskeletal impairments in Western society with a mean prevalence rate of 18.1% reported in the literature (1). Exercise therapy is suggested as an intervention for those with low back pain by the American College of Physicians and the American Pain Society (2). Hayden et al (3) suggested in their systematic review of exercise therapy effects on low back pain that strength training was mean ranked as more effective than aerobic, coordination or mobilization training. Whole body strength training (4) has been shown to have positive impacts on low back pain. However, the use of free weight compound weight lifting exercises as the primary strength training tool in an intervention has limited coverage. Objectives: The aim of the current study is to investigate the effects of a free weight based strength training intervention on pain, low back muscular endurance, lumbar fat infiltration and biomechanics. Methods: Participants had presented to their physician with low back pain that had lasted for longer than 3 months with or without radicular pain, and were between 16 and 60 years of age. Exclusion criteria were previous spinal surgery, tumours, nerve root entrapment accompanied by neurological deficit, spinal infection and inflammatory disease of the spine. Throughout the study they filled out a visual analogue scale (VAS), an Oswestry Disability Index (ODI) questionnaire and a Euro-Qol v2 questionnaire as measures of pain, disability and quality of life. Kinematic and kinetic data for 3 bodyweight squats. Participants then completed a Biering-Sorensen (BS) test. The participants then completed 16 weeks of free weight whole body resistance training. Magnetic resonance images were obtained prior to and post intervention in order to measure lumbar fat infiltration. This was measured at L3/L4, L4/L5 and L5/S1 levels. Region of interest was the area of erector spinae and multifidus and percentage fat infiltration was calculated. Results: Significant (p≤0.05) improvements of 72%, 76% and 27% were seen in VAS, ODI and Euro-Qol respectively. A significant (p≤0.05) increase of 20% in BS time to exhaustion was observed but no significant increase was seen in maximum force produced in the mid thigh pull. Significant reductions (p≤0.05) were seen in percentage fat infiltration bilaterally at the L3/L4 (left 23% right 22%) and L4/L5 (left 18% right 14%) levels. Significantly (p≤0.05) lower squats were seen across the group. Conclusions: This study demonstrates that whole body, free weight resistance training can be used as an effective tool for rehabilitating those with low back pain. Improvements are multifactoral and include changes in muscle physiology, biomechanics and muscular endurance. References: Hoy et al (2010) The Epidemiology of low back pain. Best Pract Res Clin Rheum. 24(6):769–812. Chou R, et al (2007) Diagnosis and Treatment of Low Back Pain. Ann Intern Med. 147(7):478–91. Hayden JA, et al (2005) Systematic Review: Strategies for Using Exercise Therapy To Improve Outcomes in Chronic Low Back Pain. Ann Intern Med. 142(9):776–85. Kell RT, et al (2001) The Response of Persons With Chronic Nonspecific Low Back Pain to Three Different Volumes of Periodised MSK Rehabilitation. J Str Cond Res. 2011;25(4):1052–64 Disclosure of Interest: None declared